Effect of temperature on the lipolytic and proteolytic activity of Bacillus cereus isolated from dairy products - Montanhini, M. T M; Montanhini, R. N.; Pinto, J. P N [UNESP]; Bersot, L. S. (My University, 2013)
Bacillus cereus is a bacterium with deteriorating potential for dairy products, by being a psychrotrophic organism producer of lipases and proteases. This study evaluated the psychrotrophic behavior, lipolytic and proteolytic activity at 30°C, 10°C and 7°C of 86 strains of B. cereus lato sensu isolated from dairy products, marketed in Southern Brazil. It was also evaluated the optimal temperature for protease production. No strain grew at 7°C; but at 10°C, 84.9% of strains have grown. Only one strain had lipolytic activity at 30°C, and none at 7°C. At 10°C, 16.3% of strains produced lipases. All the strains presented proteolytic activity at 30°C; and at 10°C, 72.1% had this activity, and at 7°C, only 4.6%, an amount significantly lower (p < 0.05). The temperature of 20°C promoted the highest proteolytic activity, and at 10°C, the lowest activity. B. cereus can produce lipases and proteases at room and marginal chilling temperatures, causing technological defects in dairy products stored under these conditions. © 2008 IFRJ.
Keywords: Chilling; Lipase; Protease